ANALISIS PERILAKU BRAND SWITCHING KONSUMEN MCDONALD'S DI TENGAH KONFLIK ISRAEL–PALESTINA DENGAN MENGGUNAKAN PENDEKATAN THEORY OF PLANNED BEHAVIOR : (Studi Kasus Pada Gen Z di Kota Depok Bulan Oktober 2023–Januari 2024) - Adawiyah, Endah wardatul; Purwinarti, Titik; Rosalina, Erlyn; Ginting, Riskon (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
ABSTRACT : The purpose of this study is to identify the consumption habit and tendencies of Gen Z in Depok in responding to the Israeli-Palestinian conflict, which influence their decision to remain loyal to or switch from McDonald's. Data from 100 respondents were assassed using the PLS-SEM method. The outcomes of the analysis show that Attitude towards behavior shows a positive and significant effect on Brand switching behavior, from a coefficient value of 0.226 and P values of 0.012. Subjective norms variable is positive and significant on Brand switching behavior, with a coefficient of 0.365 and P values of 0.000. In addition, Perceived behavioral control also shows a positive and significant effect on Brand switching behavior, from the coefficient value which indicates 0.375 with P values of 0.000. These findings suggest that Gen Z is more likely to switch brands if they feel their attitude towards McDonald's is negative, are influenced by social norms, and feel they have control in the decision.